Alur Rantai Pasok Kentang Granola Di Desa Sumber Rejo Kecamatan Ijen Kabupaten Bondowoso - Purwatiningsih, Rini; Prawiro, Tono Adi (Universitas Panca Marga, 2022)
The trend of consumption of fresh granola potatoes in Indonesia had increased. The consumption of granola potatoes which tends to increase was inversely proportional to the national production of granola potatoes. Various reasons was the cause of the decline in granola potato production. One of the off farm factors was how the distribution of potatoes reaches consumers. Research objectives: (1)Knowing the supply chain flow of potato granola commodity production. (2) Knowing the flow of the potato granola commodity financial chain. (3) Knowing the information chain flow of potato granola commodity. The determination of the research area was purposive methods, namely the supply chain flow of granola potatoes from harvesting on land located in Sumber Rejo Village, Ijen District until the granola potatoes were in the main market of Bondowoso Regency. The sampling method used the snowball sampling method, while data analysis used descriptive qualitative methods.Results: (1) Supply chain flow on potato granola production: (a) Farmers – seed suppliers; (b) Farmers – collectors – wholesalers – retailers –consumers. (2) There are five financial chain lines on potato granola production: (a) Farmer Level; (b) Supplier level; (c) wholesalers level; (d) Retailer level; (e) consumers level. (3) There are four lines of information chain on potato granola production: (a) Farmer – supplier; (b) suppliers - wholesalers; (c) wholesalers - retailers; (d) retailers - consumers Keywords: Granola Potato. Ijen District